HUBUNGAN ANTARA TINGKAT STATUS SOSIAL EKONOMI KELUARGA DENGAN DISIPLIN MELAKSANAKAN SHALAT BERJAMAAH SISWA KELAS XI DI MA N BOYOLALI - Juanita Andan; Retno Wahyuningsih (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The abstract research to know and test the social status relationship of the family's economics with discipline to perform moldy prayers, Social status economics on the discipline of guilds in MAN 3 boyolali 2020 / 2021.This research uses a quarantinative approach., The sample in this study was 78 responders from the population of 98 xi class students in MAN 3 Boyolali 2020 / 2021 with questionnaire data collection techniques and sampling techniques using prompling techniques.Data analysis uses the coruct moment correlation analysis with the application prop sps version 26.0 of this study shows: a ) the economic status rate of the student family of xi in man boyolali 2020 / 2021 is divided into the middle category of 57 families (73 %) with the average value of 85.32.Middle value of 83.5.Mode value of 80.65 with 9.28 deviation standard. B ) discipline performs moldy prayer students of the xi class in MAN 3 Boyolali 2020 / 2021 is a medium category of 57 students (73 %) with an average value of 89.53. Mid value is 91.15..Mode value of 99.67 with standard deviation 8.9. C ) Based on the result of the production point correlation got the value of r count by 0.309 then it was consulted with r tables at n = 78 and the signification of 5 % by 0.2199.Because > so the alternative hypothesis is accepted is that there's a positive relationship between the social status rate of the family's economics and discipline to perform the secular prayer of xi students in the madrassa aliya of the boyololi state of 2020 / 2021.Keyword: economic social status level, Discipline performs moldy prayers. 2020 / 2021 is a medium category of 57 students (73 %) with an average value of 89.53.Mid value is 91.15..Mode value of 99.67 with standard deviation 8.9. C ) Based on the result of the production moment correlation got the value of r count by 0.309 then it was consulted with r tables at n = 78 and the signification of 5 % of 0.2199. Because > so the alternative hypothesis is accepted is that there's a positive relationship between the social status rate of the family's economics and discipline to perform the secular prayer of xi students in the madrassa aliya of the Boyololi state of 2020 / 2021.